On the influence of anchor ice in relation to fish offal and the Newfoundland fisheries [electronic resource] - Hind, Henry Youle, 1823-1908. (St. John's, Nfld. : [s.n.], 1877)
"Part II"--p. 1. Includes bibliographical references. Electronic reproduction. Mode of access: Internet. 44